Principles of Strategy Formation and Tools for the Analysis and Forecasting of Work of Organizations Engaged in Energy Sales Activities - Kravchenko, Oksana A. (International Journal of Energy Economics and Policy, 2019)
The paper shows the urgency of the development of methodology and tools of strategic management for the organizations engaged in energy sales activities. These organizations' principles of strategy formation are listed here, and their priority is shown. The following tools for the analysis and forecasting of the functioning for the organizations performing power sales activity are offered: methods of the theory of probability, mathematical statistics, and rank analysis. The authors present the results of these methods' application in assessing the effectiveness of the indicator of guaranteeing suppliers' net profitability of sales in 2017. Analysis of the net return on sales of guaranteeing suppliers, as one of the performance indicators, showed that the mathematical expectation of this value decreased from 0.97 % in 2012 to 0.41% – in 2017. The authors also propose an adapted algorithm for predicting the net profitability of the sales for the organizations involved in energy supply activities. Keywords: Mathematical Statistics, Adapted Algorithm, Development. JEL Classifications: Q40; Q47; C02 DOI: https://doi.org/10.32479/ijeep.8445